The peanut butter falcon [videorecording (DVD)] - Nilson, Tyler, 1981-; Schwartz, Michael (Michael David), 1978-; LaBeouf, Shia, 1986-; Johnson, Dakota, 1989-; Hawkes, John, 1959-; Dern, Bruce (Lionsgate, 2019)
An adventure story set in the world of a modern Mark Twain that begins when Zak, a young man with Down syndrome, runs away from a nursing home where he lives to chase his dream of becoming a professional wrestler and attending the wrestling school of The Salt Water Redneck, his idol. Through circumstances beyond their control, Tyler, a small-time outlaw on the run, becomes Zak's unlikely coach and ally.